2014
DOI: 10.1039/c4cp02095b
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Cr(iii) catalyzed isomerization mechanism of glucose to fructose in the presence of water using ab initio molecular dynamics

Abstract: The mechanism of glucose ring opening and isomerization to fructose, catalyzed by the Lewis acid catalyst CrCl3 in the presence of water, is investigated using Car-Parrinello molecular dynamics with metadynamics. Minimum energy pathways for the reactions are revealed and the corresponding free energy barriers are computed. Addition of glucose replaces two water molecules in the active [Cr(H2O)5OH](+2) complex, with two hydroxyl groups of glucose taking their place. Ring opening and isomerization reactions can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 39 publications
9
67
0
Order By: Relevance
“…12), also slows down the kinetics of side reactions and helps achieve better selectivity for the dehydration reaction. Recent investigations into CrCl 3 catalyzed glucose to fructose isomerization were performed by Mushrif et al (2014), using CPMDmetadynamics, with explicit water molecules. They demonstrated that, contrary to popular belief that the hexahydrated Cr 3 þ is the active species, the partially hydrolyzed [Cr(H 2 O) 5 OH] 2 þ complex is the active isomerization species.…”
Section: Solvent Effects On Biomass Conversion Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…12), also slows down the kinetics of side reactions and helps achieve better selectivity for the dehydration reaction. Recent investigations into CrCl 3 catalyzed glucose to fructose isomerization were performed by Mushrif et al (2014), using CPMDmetadynamics, with explicit water molecules. They demonstrated that, contrary to popular belief that the hexahydrated Cr 3 þ is the active species, the partially hydrolyzed [Cr(H 2 O) 5 OH] 2 þ complex is the active isomerization species.…”
Section: Solvent Effects On Biomass Conversion Reactionsmentioning
confidence: 99%
“…The free energy barrier for the reaction is 104 kJ/mol. The free energy surface is constructed as a function of two reaction coordinates (Mushrif et al, 2014).…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…45 It has been shown that the protonation of glucose at C 2 oxygen (carbon atom numbering same as shown in Table 2) leads to the formation of HMF, while the protonation of the oxygen attached to C 3 and C 4 leads to other dehydration/rehydration products. 19,50 For both condensation and dehydration products to be formed, water molecules need to be present in the immediate vicinity of the specic oxygen atom so that proton can be transferred from water to that oxygen atom. Qian et al have done a series of studies using Car-Parrinello molecular dynamics to study the conversion of glucose via different dehydration and condensation pathways by protonation of different oxygens.…”
Section: Atomic Details Of the Positioning Of Solvents Around Glucosementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Since cellulosic biomass and its sugar derivatives are solid species, these reactions are performed in a solvent medium. [1][2][3][4][5][6][7][8][9] Since cellulosic biomass and its sugar derivatives are solid species, these reactions are performed in a solvent medium.…”
Section: Introductionmentioning
confidence: 99%